Genome level expression profiles in pediatric septic shock indicate a role for altered zinc homeostasis in poor outcome - Wong, Hector R. (2007)
Human septic shock involves multiple genome-level perturbations. We have conducted microarray analyses in children with septic shock within 24 hours of intensive care unit admission, using whole-blood derived RNA. Based on sequential statistical and expression filters, there were 2,482 differentially regulated gene probes (1,081 upregulated and 1,401 downregulated) between patients with septic shock (n = 42) and controls (n = 15). Both gene lists encompassed several biologically relevant gene ontologies and canonical pathways. Notably, many of the genes downregulated in the patients with septic shock, relative to the controls, participate in gene ontologies related to metal or zinc homeostasis. Comparison of septic shock survivors (n = 33) and nonsurvivors (n = 9) demonstrated differential regulation of 63 gene probes. Among the 63 gene probes differentially regulated between septic shock survivors and nonsurvivors, two isoforms of metallothionein (MT) demonstrated increased expression in the nonsurvivors. Consistent with the ability of MT to sequester zinc in the intracellular compartment, nonsurvivors had lower serum zinc levels compared to survivors. In a corroborating study of murine sepsis, MT-null mice demonstrated a survival advantage compared to wild-type mice. These data represent the largest reported cohort of pediatric patients with septic shock, which has undergone genome-level expression profiling based on microarray. The data are biologically plausible and demonstrate that genome-level alterations of zinc homeostasis may be prevalent in clinical pediatric septic shock.